Unveiling the Hidden Struggles: Political Violence Against Women Through the Lens of Standpoint Theory - Umaimah, Umaimah; Zainudin, Mohamad Zahir; Sumardi, Eko; Akbar, Muhammad; Putra, Ryanka Dizayani (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Violence against women in politics is fundamentally rooted in the patriarchal socio-cultural construct that creates unfair and unequal perspectives, disadvantaging women while benefiting men. This study focuses on the violence experienced by women due to the perspectives and power relations shaped by long-standing patriarchal values. Using Standpoint Theory and the theory of power relations in communication influenced by patriarchal culture, this research analyzes how differences in viewpoints between men and women can lead to divergent ideas, attitudes, knowledge, and behaviors regarding women. The study adopts a qualitative approach using a single holistic case study method. The research object is the perspective underlying violence against women in politics. The entrenched patriarchal culture has reinforced discriminatory understanding and awareness towards women. Consequently, this study emphasizes the importance of a continuous movement to eradicate political violence, aiming to establish a political communication framework that is free from violence and equitable for all, regardless of gender.Keywords: Political Violence, Patriarchy, Political Culture, Women, Standpoint Theory AbstrakKekerasan terhadap perempuan dalam politik pada dasarnya berakar pada konstruksi sosial-budaya patriarkal yang membentuk perspektif yang tidak adil dan tidak setara, merugikan perempuan dan menguntungkan laki-laki. Penelitian ini berfokus pada kekerasan yang dialami perempuan akibat perspektif dan relasi kuasa yang dibentuk oleh nilai-nilai patriarki yang telah lama mengakar. Dengan menggunakan Teori Standpoint dan teori relasi kuasa dalam komunikasi yang dipengaruhi oleh budaya patriarkal, penelitian ini menganalisis bagaimana perbedaan sudut pandang antara laki-laki dan perempuan dapat menghasilkan ide, sikap, pengetahuan, dan perilaku yang berbeda terhadap perempuan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus holistik tunggal. Objek penelitian adalah perspektif yang melandasi kekerasan terhadap perempuan dalam politik. Budaya patriarkal yang mengakar kuat telah memperkuat pemahaman dan kesadaran diskriminatif terhadap perempuan. Oleh karena itu, penelitian ini menekankan pentingnya gerakan berkelanjutan untuk menghapus kekerasan politik, dengan tujuan membangun kerangka komunikasi politik yang bebas dari kekerasan dan adil bagi semua pihak, tanpa memandang gender.Kata kunci: kekerasan-politik, partiarki, budaya politik, perempuan, stanpoint theory